Visual attributes of formation of wine brand - Пазюк, Вікторія Леонідівна (Technology audit and production reserves, 2015)
The article is devoted to the formation of the visual attributes of wine brand, namely packaging and label. Its tasks and functions in the formation of wine brand are determined. The means of visual impact on the formation and maintenance of wine brand are investigated. It is shown that the packaging and label create new trends in communications with the consumer. It is proved that the formation of a wine brand depends not only on global trends, government regulation, development strategy, but also on the correct design and use of visual attributes. During the fierce competition in the global and domestic markets, the development of a unique visual brand image of wine is an important tool in thecompetition for the consumer. Visual attributes influence the choice of consumers, so the need for innovative approaches in creating packaging and labels is an important element in shaping the wine brand. The role and importance of visual attributes in the process of forming of wine brand are identified in the article. Thus, the modern role of packaging and label goes far beyond its former purely protective functions, scope covers promotion, extending to communications of consumer with manufacturer or seller.